Isolated tumor cells in stage I & II colon cancer patients are associated with significantly worse disease-free and overall survival. Issue 1 (December 2016) - Weixler, B.; Warschkow, R.; Güller, U.; Zettl, A.; von Holzen, U.; Schmied, B.; Zuber, M.
Abstract Background Lymph node (LN) involvement represents the strongest prognostic factor in colon cancer patients. The objective of this prospective study was to assess the prognostic impact of isolated tumor cells (ITC, defined as cell deposits ≤ 0.2 mm) in loco-regional LN of stage I & II colon cancer patients. Methods Seventy-four stage I & II colon cancer patients were prospectively enrolled in the present study. LN at high risk of harboring ITC were identified via an in vivo sentinel lymph node procedure and analyzed with multilevel sectioning, conventional H&E and immunohistochemical CK-19 staining. The impact of ITC on survival was assessed using Cox regression analyses. Results Median follow-up was 4.6 years. ITC were detected in locoregional lymph nodes of 23 patients (31.1 %). The presence of ITC was associated with a significantly worse disease-free survival (hazard ratio = 4.73, p  = 0.005). Similarly, ITC were associated with significantly worse overall survival (hazard ratio = 3.50, p  = 0.043). Conclusions This study provides compelling evidence that ITC in stage I & II colon cancer patients are associated with significantly worse disease-free and overall survival. Based on these data, the presence of ITC should be classified as a high risk factor in stage I & II colon cancer patients who might benefit from adjuvant chemotherapy.